Global Shared Service Trends in the Central and Eastern Europen Markets - Róbert Marciniak (Entrepreneurial Business and Economics Review)
The main objective of the research is to disclose what kind of trends are present in the global business service markets and which appear in the Central and Eastern European (CEE) business market. The research determines the most important business service trends that emerged in shared service organizations in the CEE region.